Meconopsis aculeata Royle an Endangered and Endemic Medicinal Plant in the Himalaya - A Review - Paul, Shiv; Lata, Swaran (Indian Forester, 2024)
The present review describes the distribution, habitat, associated species, indigenous uses, phytochemical constituents, pharmacological aspects, threat status, and conservation strategies for Meconopsis aculeata. The plant is one of the endemic and endangered medicinal plants in the Western Himalayan Region; restricted to specific areas of the Himalaya and prefers to grow in moist rocky/bouldery habitats within at an altitudinal range of 3000 - 4700 m amsl. The whole plant is used for medicinal purposes as antiinflammatory, anti-bacterial, anti-fungal, antioxidant, analgesic, tonic, poisonous, narcotic, and febrifuge. Some major associated species of M. aculeata are Danthonia schneideri, Salix denticulata, Carex sentosa, Bistorta affinis, Bistorta macrophylla, Viola biflora, Betula utilis, Abies spectabilis, Picrorhiza kurroa, Rheum emodi, Aconitum violaceum, and Rhododendron campanulatum. Habitat degradation, over exploitation, unsustainable harvesting, and over grazing are the main causes of its continuously declining population. Therefore, efforts should be made for conservation in natural habitats with the active participation of local inhabitants, the forest department, and other agencies.